STUDI EVALUASI PENGENDALIAN BIAYA (COST CONTROL) DAN JADWAL PELAKSANAAN (SCHEDULING) PADA PROYEK PEMBANGUNAN GEDUNG RAWAT JALAN DAN BASSEMENT RSUD MAJALENGKA MENGGUNAKAN METODE EARNED VALUE DAN SOFTWARE MS. PROJECT : Indonesia - Arief Rijaluddin (J-ENSITEC, 2021)
Planning and controlling costs and time is part of the overall construction project management. In addition to the assessment in terms of quality, the achievement of a project can also be assessed in terms of cost and time. The costs that have been incurred and the time spent in completing a job must be measured continuously for deviations from the plan. The presence of significant cost and time deviations indicates poor project management. With the existence of project performance indicators in terms of cost and time this allows preventive actions so that project implementation goes according to plan. The concept of "Earned Value" is one of the tools used in project management that integrates cost and time and by using Ms. Projects. Ms. Project is a project management software product and is developed and sold by Microsoft. It is designed to assist a project manager in developing plans, assigning resources and tasks, tracking progress, managing budgets and analyzing workloads. From the results of the evaluation of cost control and project schedules on outpatient and basement building construction projects using the earned value method, it can be concluded that the CV (Cost Variant) in this project results in 0 which means the Zero Number on the Cost Variant indicates that the cost is within the budget, SV (Schedule). Variant ) the value shows a negative number, this means that the completion of the work is delayed, the CPI (Cost Performance Index) is 1, meaning that the expenditure is in accordance with the project budget